Making Tangible the Intangible: Hybridization of the Real and the Virtual to Enhance Learning of Abstract Phenomena - Fleck, Stéphanie; Hachet, Martin (Frontiers in ICT, 2016)
Interactive systems based on augmented reality (AR) and tangible user interfaces (TUI) hold great promise for enhancing how to learn and understand abstract phenomena. In particular, they combine the advantages of numerical simulation and pedagogical support while keeping the learner involved in true physical experimentation. In this paper, we discuss three examples of such AR and TUI systems that address hardly perceivable concepts. The first example, Helios, targets K-12 learners in the field of astronomy. The second one, Hobit, is dedicated to experiments in wave optics. Finally, the third one, Teegi, allows one to get to know more about brain activity. These three hybrid interfaces have emerged from a common basis that jointly combines research and development work in the fields of instructional design and human–computer interaction (HCI), from theoretical to practical aspects. Based on investigations carried out in the context of real use and grounded on works in education and HCI, we formalize how and why the hybridization of the real and the virtual leverages the way learners understand intangible phenomena in Science education.